Momentum profitability in Malaysia - Tan, Yeng May; Cheng, Fan Fah; Hassan, Taufiq (Universiti Putra Malaysia Press, 2014)
This paper reports evidence of short-term momentum profits in a study of 700 stocks traded in the emerging Malaysian stock market. For this purpose, momentum portfolios were formed over a full sample period and other sub-periods that included the Asian Financial Crisis, Global Financial Crisis and the period between the two crises. Significant negative returns were observed during the economic downturn brought about by the Asian Financial Crisis, consistent with literature. Moreover, the results showed positive returns over the period characterised by rising market index. This finding is consistent with publication and may be explained as due to investors' confidence being high in a rising market. In addition, individual stock momentum observed was studied to determine whether it was attributable to industry effect, which is a less explored topic. The results of the current study showed that strategies of buying past winning industries and selling past losing industries appeared to be profitable in this market. Thus, this research's findings have added to the literature on this topic from an emerging market place.